2012
DOI: 10.1103/physrevb.85.115412
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium-reduced density matrix formulation: Influence of noise, disorder, and temperature on localization in excitonic systems

Abstract: An exact method to compute the entire equilibrium reduced density matrix for systems characterized by a system-bath Hamiltonian is presented. The approach is based upon a stochastic unraveling of the influence functional that appears in the imaginary time path integral formalism of quantum statistical mechanics. This method is then applied to study the effects of thermal noise, static disorder, and temperature on the coherence length in excitonic systems. As representative examples of biased and unbiased syste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
125
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 106 publications
(130 citation statements)
references
References 52 publications
5
125
0
Order By: Relevance
“…26,[32][33][34][35][36] Using a Hubbard-Stratonovich transformation, 26,32,34,37 it was shown that the influence functional may be unraveled by an auxiliary stochastic field. The ensuing imaginary time evolution may then be interpreted as one governed by a time-dependent…”
Section: Discussionmentioning
confidence: 99%
“…26,[32][33][34][35][36] Using a Hubbard-Stratonovich transformation, 26,32,34,37 it was shown that the influence functional may be unraveled by an auxiliary stochastic field. The ensuing imaginary time evolution may then be interpreted as one governed by a time-dependent…”
Section: Discussionmentioning
confidence: 99%
“…Without trapping, hopping kinetics always imposes P n (t → ∞) ∝ exp(−βε n ). Instead, the quantum steady-state distribution is evaluated by ρ(t → ∞) ∝ Tr B {exp(−βH tot )}, which arises from the rigorous quantum Boltzmann distribution with the consideration of both system and bath [53]. The steady-state population of the lowest energy trap site can be decreased, implying a lower probability of energy being trapped (energy transfer efficiency).…”
Section: A Trapping Timementioning
confidence: 99%
“…Consequently, the equilibrium population predicted by the RQKE rate can deviate from the classical Boltzmann distribution and approach to the exact quantum Boltzmann distribution, P eq;n ∝ [Tr B {exp(− βH tot )}] nn . 39,40 As a verification, we extend our previous study at a high temperature T = 300 K to lower temperatures. Since the equilibrium population is always one half in the unbiased system, we only consider the biased system, ε 12 = 100 cm −1 , with J = 100 cm −1 and λ = 100 cm −1 .…”
Section: Temperature Dependence Of the Quantum Equilibrium Populationmentioning
confidence: 72%
“…The hierarchy equation with the Matsubara frequency summation is used to obtain the exact equilibrium population, which is numerically the same as the result of the stochastic path integral. 39,40 Our numerical calculation shows that each correction term δ 2 j(<k−1) is different for the forward and backward rates, and the deviation increases as temperature decreases. As shown in Fig.…”
Section: Temperature Dependence Of the Quantum Equilibrium Populationmentioning
confidence: 99%
See 1 more Smart Citation